Plasma Hormone and Metabolomics Identifies Metabolic Pathways Associated with Growth Rate of Dezhou Donkeys - Liyuan Wang; Tong Li; Qiugang Ma; Honglei Qu; Changfa Wang; Wenqiang Liu; Wenqiong Chai (Animals)
Background: The growth traits of donkeys from the same farm under the same feeding conditions often vary. Methods: In this study, Plasma hormone level and LC–MS-based metabolomics was used to identify the metabolic pathways and the key metabolites associated with the growth rate of Dezhou donkeys. Results: The level of IGF-1 in the SG was significantly higher than that in the FG. The differentially abundant metabolites were related mainly to lipid metabolism, in which arachidonic acid metabolism, linoleic acid metabolism and steroid hormone biosynthesis played key roles. The main differentially abundant metabolites 2,3-dinor-8-iso-PGF2α, 11-DH-TXB2, 8(R)-HPETE, PGJ2, c9, t11-CLA, 12,13-DHOME, 9,10-DHOME, 9(10)-EpOME, 13-HPODE, DHEAS, testosterone, and corticosterone played important roles in metabolic homeostasis and affected the adaptation of donkeys to cold environments. Conclusions: The present study revealed that the growth rate of donkeys is mainly influenced by their adaptation to the environment, providing a more in-depth study on the relationship between plasma metabolomics and growth rate in donkeys.